Handbook of Photovoltaic Silicon - Yang, Deren (Springer Berlin Heidelberg : Imprint: Springer, 2019)
The utilization of sun light is one of the hottest topics in sustainable energy research. To efficiently convert sun power into a reliable energy - electricity - for consumption and storage, silicon and its derivatives have been widely studied and applied in solar cell systems. This handbook covers the photovoltaics of silicon materials and devices, providing a comprehensive summary of the state of the art of photovoltaic silicon sciences and technologies. This work is divided into various areas including but not limited to fundamental principles, design methodologies, wafering techniques/fabrications, characterizations, applications, current research trends and challenges. It offers the most updated and self-explanatory reference to all levels of students and acts as a quick reference to the experts from the fields of chemistry, material science, physics, chemical engineering, electrical engineering, solar energy, etc.